2021
DOI: 10.1186/s12913-021-06313-7
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Ghanaian traditional health practitioners, primary health care workers, service users and caregivers regarding collaboration for mental health care

Abstract: Background In low- and middle-income countries, the paucity of conventional health services means that many people with mental health problems rely on traditional health practitioners (THPs). This paper examines the possibility of forging partnerships at the Primary Health Care (PHC) level in two geopolitical regions of Ghana, to maximize the benefits to both health systems. Methods The study was a qualitative cross-sectional survey. Eight (8) focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 33 publications
(39 reference statements)
3
15
0
Order By: Relevance
“…As revealed in a study, orthodox medicine has fallen below expectations of patients and their caregivers, and both groups of practitioners also expressed reservations regarding collaboration. 41 In general, observations from this study align with those of recent scoping reviews of the knowledge and attitude towards mental illness in Nigeria. 42,43 The reviews covered institutional and community levels in different parts of the country.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As revealed in a study, orthodox medicine has fallen below expectations of patients and their caregivers, and both groups of practitioners also expressed reservations regarding collaboration. 41 In general, observations from this study align with those of recent scoping reviews of the knowledge and attitude towards mental illness in Nigeria. 42,43 The reviews covered institutional and community levels in different parts of the country.…”
Section: Discussionsupporting
confidence: 86%
“…As revealed in a study, orthodox medicine has fallen below expectations of patients and their caregivers, and both groups of practitioners also expressed reservations regarding collaboration. 41 …”
Section: Discussionmentioning
confidence: 99%
“…In line with previous research on general mental health [31,32], all stakeholders report serious concerns regarding shared management of psychotic patients [20 ▪ ,41 ▪ ]. In Ghana, TFH, patients and caregivers mentioned fear of disrespect and undue criticism by biomedical practitioners as important obstacles, while primary health providers mentioned the potential harm of traditional treatments [20 ▪ ]. As opposed to reports on general mental health [32], a study at a holy water site in Ethiopia, where mostly psychotic patients were treated, reported that incompatibility of beliefs was an important reason for resistance among some of the holy water attendants to refer patients to the psychiatric clinic [41 ▪ ].…”
Section: Recent African Studiessupporting
confidence: 67%
“…In line with previous research on general mental health [31,32], all stakeholders report serious concerns regarding shared management of psychotic patients [20 ▪ ,41 ▪ ]. In Ghana, TFH, patients and caregivers mentioned fear of disrespect and undue criticism by biomedical practitioners as important obstacles, while primary health providers mentioned the potential harm of traditional treatments [20 ▪ ].…”
Section: Recent African Studiessupporting
confidence: 66%
“…While there is growing evidence which shows that traditional treatments conducted by THPs are either innocuous or beneficial in the field of mental health ( 52 , 53 ), there are also reports which show that some forms of traditional health approaches include treatment methods that are potentially harmful, or that detract from due attention to the human rights of patients with serious mental disorders ( 52 , 54 ). Therefore, we devoted a lot of time and effort to ensure positive collaboration and patient safety with a selected group of THPs in the region.…”
Section: Discussionmentioning
confidence: 99%